Location and excavating site preparation - Shopware (Firm) (New Jersey : Shopware Productions, 2004)
This informative video looks at considerations that go into choosing a structure's location, as well as that first big step on-site: breaking ground
Title from title screen
Teacher's guide online on www.shopware.usa.com
DVD format
Keywords: House construction; Land use -- Planning; Siding (Building materials); Building trades